PENGOLAHAN DAN PENJERNIHAN AIR DENGAN MEMANFAATKAN MEDIA CANGKANG KERANG BULU - Putra, Yulianto Laksono; Abdullah, Abdul Aziz; Hermawan, Wawan (Sains & Matematika, 2013)
In Desa Pademonegoro, Kecamatan Sukodono, Sidoarjo the quality of water reservoir consumpted by many people is found to be in a low level and contains unnecessary substances like Mn and Fe. This condition makes water not feasible to consumpt for daily use. This study aimed to manage and purify water by utilizing ark shells freely available in beaches. Ark shells were initially synthesized by coprecipitation techniques using carbon dioxide gas at a pressure of 225 N/cm2, 300N/cm2,or 375 N/cm2 and settling time for 24 hoursor 36 hours. The ark shells were then characterized using X-Ray Diffraction (XRD) to determine its CaCO3 content. The ark shells with a high level of CaCO3 were used as a water purifier on the device spesificially designed on purpose and were tested with shell powder thickness with a thickness of 1 cm, 3 cm, or 5 cm and a water reservoir was placed at a position of 1 m or 2 m measured from the ground. The results indicated that the synthesis of ark shell using carbon dioxide at a pressure of 375 N/cm2and settling time for 36 hourshada high level of CaCO3 and thus was used as a water purifier. After purifying, the quality of water is such that it is odorless and tasteless, its color<2 TCU, turbidity of 0.2 NTU, TDS of 200 mg/l, contains Fe 0.08 mg/l, Mn0.03 mg/l, Hg 0.0001mg/l,As<0.005mg/l, pH 7.3, detergent <0.01 mg/l, water hardness of 88.32 mg/land saturation ark shells for 27 weeks.